2022
DOI: 10.1126/science.abm3087
|View full text |Cite
|
Sign up to set email alerts
|

Indirect protection of children from SARS-CoV-2 infection through parental vaccination

Abstract: Children unvaccinated against SARS-CoV-2 may still benefit through protection from vaccinated contacts. We estimated the protection provided to children through parental vaccination with the BNT162b2 vaccine. We studied households without prior infection, consisting of two parents and unvaccinated children, estimating the effect of parental vaccination on the risk of infection for unvaccinated children. We studied two periods separately– an early period (January 17, 2021 - March 28, 2021, Alpha variant, two do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 38 publications
5
32
0
Order By: Relevance
“…In preceding literature, vaccination was associated with a reduction in transmission of the alpha and the delta variants [29]. Parental vaccination confers substantial protection on unvaccinated children in the household [30]. Viable delta variant virus was detected for a notably longer duration in partially vaccinated and unvaccinated individuals compared with fully vaccinated individuals [31].…”
Section: Discussionmentioning
confidence: 96%
“…In preceding literature, vaccination was associated with a reduction in transmission of the alpha and the delta variants [29]. Parental vaccination confers substantial protection on unvaccinated children in the household [30]. Viable delta variant virus was detected for a notably longer duration in partially vaccinated and unvaccinated individuals compared with fully vaccinated individuals [31].…”
Section: Discussionmentioning
confidence: 96%
“…Identification of the nature of vaccine waning ( 4 ) led Israeli authorities to initiate an extensive booster campaign that curtailed the Delta resurgence. Previous studies have quantified the effects of boosting on an individual level ( 5 , 10 , 11 ). Here, we expand our understanding to the population level by constructing a mathematical model that accurately describes the Delta surge dynamics in Israel.…”
Section: Discussionmentioning
confidence: 99%
“…The direct protection of the booster has been estimated in both clinical trials and observational studies ( 5 , 12 , 13 ). Indirect protection due to parental vaccination was estimated in household studies ( 10 , 11 ). Similarly, the household study ( 14 ) found that the odds ratio of a secondary case in a vaccinated individual was 0.54 of an unvaccinated individual.…”
Section: Discussionmentioning
confidence: 99%
“…Whether antibody transfer mediates host protection will be a function of exposure, but it seems reasonable to suggest, all things being equal, that any amount of antibody transfer would prove useful to the recipient host. A recent publication showed substantial benefits of parental vaccination in reducing the risk of infection in the unvaccinated children in the same home 6 . It is tempting to speculate that aerosol-mediated antibody transfer may have possibly contributed to their findings reported.…”
Section: Discussionmentioning
confidence: 99%